Case 3458: Balintus D’Abrera, 2001, Gulliveria D’Abrera & Bálint, 2001, Salazaria D’Abrera & Bálint, 2001, Megathecla Robbins, 2002 and Gullicaena Bálint, 2002 (Insecta, Lepidoptera, Lycaenidae): proposed establishment of availability - Robbins, Robert K; Lamas, Gerardo (Bulletin of Zoological Nomenclature, 2008)
The purpose of this application, under Articles 10.1, 13.1 and 81.1 of the Code, is to stabilise the usage of five generic names of Neotropical butterflies by ruling that they are available from their original descriptions. D’Abrera (2001) and D’Abrera & Bálint (2001) proposed eight generic names in the Lycaenidae [Leach], [1815] in which they differentiated the type species, not the genus. The availability of some of these names has subsequently been interpreted differently by different authors. One of these generic names, Salazaria D’Abrera & Bálint, 2001, is widely used on websites. A second, Balintus D’Abrera, 2001, has been treated as a nomenclaturally and taxonomically valid genus. A third, Gulliveria D’Abrera & Bálint, 2001, is a junior homonym that was replaced with Megathecla Robbins, 2002 and Gullicaena Bálint, 2002. However, differentiating the type species does not satisfy the requirements of Article 13.1 of the Code, so all these names are unavailable. To promote nomenclatural stability, the Commission is requested to rule that the generic names Balintus D’Abrera, 2001, Gullicaena Bálint, 2002, Gulliveria D’Abrera & Bálint, 2001, Megathecla Robbins, 2002 and Salazaria D’Abrera & Bálint, 2001 are available and place Balintus D’Abrera, 2001, Salazaria D’Abrera & Bálint, 2001, Megathecla Robbins, 2002 and Gullicaena Bálint, 2002 on the Official List of Generic Names in Zoology, and to place Annamaria D’Abrera & Bálint, 2001, Chopinia D’Abrera, 2001, Gulliveria D’Abrera & Bálint, 2001, Lucilda D’Abrera & Bálint, 2001, Pedusa D’Abrera, 2001 and Riojana D’Abrera & Bálint, 2001 on the Official Index of Rejected and Invalid Generic Names in Zoology.
Keywords: Nomenclature; taxonomy; LYCAENIDAE; Annamaria; Balintus; Chopinia; Eucharia; Gullicaena; Gulliveria; Lamasina; Lucilda; Megathecla; Pedusa; Riojana; Salazaria; hairstreak butterflies; Neotropics